Suppressing mosquito disease vectors via manipulating fertility, sex and male-courtship drive - Montell, Craig (Henry Stewart Talks, 2018)
Mosquitoes are the most dangerous animals in the world, Aedes aegypti spread Dengue, Zika and other viral-borne diseases, Suppression of Aedes through release of genetically engineered males in ways to prevent their persistence in the environment